Catalyst-free organic synthesis - Brahmachari, Goutam (Green chemistry series., 2018)
Explaining methods for carrying out chemical syntheses without the use of catalysts, this book shows how avoiding catalysts during synthesis can mean less use of toxic chemicals, environmentally damaging chemicals, or endangered elements, and lower costs.